Validation of the South Asian cichlid genus Pseudetroplus Bleeker (Pisces: Cichlidae) - Pethiyagoda, Rohan; Maduwage, Kalana; Manamendra-Arachchi, Kelum (Zootaxa, 2014)
The South Asian Cichlidae are composed of two clades that together represent the sister group of the Madagascan genus Paretroplus Bleeker. Chaetodon suratensis Bloch and Etroplus canarensis Day are retained in Etroplus Cuvier, while Chaetodon maculatus Bloch is allocated to Pseudetroplus Bleeker. Pseudetroplus is distinguished from Etroplus in having, among other characters, 11 (vs. 12–13) pleural ribs; 26–27 (vs. 28–29) vertebrae; the anterior half of the median suture between the lower pharyngeal jaw serrated (vs. smooth); the first 6 anal-fin pterygiophores arranged anterior to the first 3 (vs. 2) haemal spines; the supraoccipital-exoccipital prong extending ventrally about half-way across the foramen magnum (vs. not extending into the foramen magnum); and the anterior jaw teeth tricuspid, acuminate (vs. unicuspid, spatulate). Microgaster Swainson is a synonym of Pseudetroplus and a junior homonym of Microgaster Latreille in Hymenoptera.